POSSESSIVE DECLENSION IN KOREAN AND UZBEK: SYNTACTIC AND PRAGMATIC ASPECTS (International journal of artificial intelligence, 2025)
This paper explores the syntactic and pragmatic functions of possessive markers in Korean and Uzbek, two typologically distinct languages. It examines how these markers, through their declension, contribute to grammatical structure, semantic interpretation, and discourse coherence. The analysis focuses on the agreement patterns, scope relations, and information structure sensitivity associated with possessive constructions in both languages. Furthermore, it investigates how possessive markers contribute to pragmatic effects such as topic marking, emphasis, and conveying speaker attitudes. By comparing and contrasting the use of possessives in Korean and Uzbek, the paper aims to shed light on cross-linguistic variations and universals in the expression of possession and its role in discourse management. This comparative approach facilitates a deeper understanding of the grammatical and communicative strategies employed by speakers of Korean and Uzbek to encode possessive relationships and manage information flow.